CFD simulation of particle mixing in a fluidized bed - Kong, Deyi (2013)
This project is to do the research of CFD simulation of particle mixing in a fluidized bed.Nowadays, fluidized bed is widely used in different kinds of industry, such aspower plant, petroleum industry and food processing industry. The objectives of this project are to study the mixing and segregation phenomena in a fluidized bed and to design distributors with low pressure drop operation. Fluidized beds suspend solid fuels on upward-blowing jets of air during the combustion process. The main characteristicof fluidized bed are pressure drop, fluid velocities, bubble size and bed heightComputational fluid dynamics (CFD) simulation is the method to study this project. Firstly, Ergun 6.2 software is used to study particle mixing and segregation phenomenaSecondly, 3D geometry of fluidized bed is drawn by using Solidworks 2012. Flowsimulation program is used to study pressure drop in the fluidized bed 3D drawing.Minimum fluidized velocity and operation point is found by using Ergun 6.2 softwarePressure drop is found by using Flow Simulation program. Compare with otherresearcher ’s results these simulation results are accepted.